Potential of Natural Alkaloids From Jadwar (Delphinium denudatum) as Inhibitors Against Main Protease of COVID-19: A Molecular Modeling Approach - Kumar, Anuj; Sharma, Mansi; Richardson, Christopher D.; Kelvin, David J. (Frontiers in Molecular Biosciences, 2022)
The ongoing pandemic coronavirus disease (COVID-19) caused by a novel corona virus namely, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has had a major impact on global public health. COVID-19 cases continue to increase across the globe with high mortality rates in immunocompromised patients. There is still a pressing demand for drug discovery and vaccine development against this highly contagious disease. To design and develop antiviral drugs against COVID-19, the main protease (Mpro) has emerged as one of the important drug targets. In this context, the present work explored jadwar (Delphinium denudatum) derived natural alkaloids as potential inhibitors against Mpro of SARS-CoV-2 by employing a combination of molecular docking and molecular dynamic simulation-based methods. Molecular docking and interaction profile analysis revealed strong binding on the Mpro functional domain with four natural alkaloids viz. panicutine (-7.4 kcal/mol), vilmorrianone (-7.0 kcal/mol), denudatine (-6.0 kcal/mol), and condelphine (-5.9 kcal/mol). Molecular docking results evaluated by using MD simulations on 200 nanoseconds confirmed highly stable interactions of these compounds with the Mpro. Additionally, mechanic/generalized/born/poisson-boltzmann surface area (MM/G/P/BSA) free energy calculations also affirm the docking results. Natural alkaloids explored in the present study possess the essential drug likeness properties including absorption, distribution, metabolism, and excretion (ADME) and are in accordance with Lipinski’s rule of five. The results of this study suggest that these four bioactive molecules, condelphine, denudatine, panicutine and vilmorrianone, might be effective candidates against COVID-19 and can be further investigated using a number of experimental methods.